2014
DOI: 10.1039/c4fo00032c
|View full text |Cite
|
Sign up to set email alerts
|

Dietary sweet potato (Ipomoea batatas L.) leaf extract attenuates hyperglycaemia by enhancing the secretion of glucagon-like peptide-1 (GLP-1)

Abstract: 'Suioh', a sweet potato (Ipomoea batatas L.) cultivar developed in Japan, has edible leaves and stems. The sweet potato leaves contain polyphenols such as caffeoylquinic acid (CQA) derivatives. It has multiple biological functions and may help to regulate the blood glucose concentration. In this study, we first examined whether sweet potato leaf extract powder (SP) attenuated hyperglycaemia in type 2 diabetic mice. Administration of dietary SP for 5 weeks significantly lowered glycaemia in type 2 diabetic mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 52 publications
0
49
1
Order By: Relevance
“…Administration of sulfonylurea was found to cause hypoglycemia by strongly inducing insulin secretion even when glucose was not given, whereas SP alone did not cause hypoglycemia. These results provide evidence that the mechanism of diabetes prevention and suppression in SP involves the stimulation of GLP‐1 secretion, and the promotion of insulin secretion when blood glucose is high, leading to the normalization of blood glucose level (Fig. ).…”
Section: Dietary Factors and Stimulation Of Glp‐1 Secretionmentioning
confidence: 63%
“…Administration of sulfonylurea was found to cause hypoglycemia by strongly inducing insulin secretion even when glucose was not given, whereas SP alone did not cause hypoglycemia. These results provide evidence that the mechanism of diabetes prevention and suppression in SP involves the stimulation of GLP‐1 secretion, and the promotion of insulin secretion when blood glucose is high, leading to the normalization of blood glucose level (Fig. ).…”
Section: Dietary Factors and Stimulation Of Glp‐1 Secretionmentioning
confidence: 63%
“…Six‐week‐old male Sprague‐Dawley (SD) rats (Japan SLC, Hamamatsu, Japan; n = 16) were maintained in an air‐conditioned environment (23 ± 3°C) under an automatic lighting schedule (08:00–20:00 light) with free access to water and a standard laboratory diet (MF, Oriental Yeast Co., Ltd., Tokyo, Japan). IPGTT was conducted using our previous published process (Kato, Nakanishi, Tani, & Tsuda, ; Kato, Nishikawa, et al., ; Nagamine et al., ). Briefly, rats were deprived of food for 13 hr at 7 weeks of age, before oral administration by direct stomach intubation of vehicle (control; 0.9% NaCl) or BCE 5 mg/kg body weight (1 mg D3R/kg body weight).…”
Section: Methodsmentioning
confidence: 99%
“…After 30 min, rats received IP administration of glucose solution (2 g/kg). Blood samples were collected at 0 (before glucose loading), 15, 30, 60, and 120 min after glucose injections, and serum glucose and insulin concentrations were measured with Glucose CII‐Test (Wako) and Ultra Sensitive Rat Insulin ELISA kit (Morinaga Institute of Biological Science, Yokohama, Japan), respectively (Kato, Nakanishi et al., ; Kato, Nishikawa, et al., ; Nagamine et al., ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is suggested that anthocyanins, as natural pigments, may provide beneficial health effects. Studies proved anthocyanin provide physiological functions such as antihyperglycemic [4], antiinflamatory and anticarcinogenic [5] and antioxidant [6].…”
Section: Introductionmentioning
confidence: 99%